ASTROVIRUS INFECTION IN CHILDREN IN LAGOS, NIGERIA - Ayolabi, C. I; Ojo, D A; Akpan, I (African Journal of Infectious Diseases (AJID), 2011)
A preliminary investigation was conducted to screen for astrovirus in Lagos. Two hundred and fifteen (215) faecal samples collected from children under 5 years old with diarrhoea (161) and without diarrhoea (54) admitted at paediatric clinics in Lagos State were studied. The stool specimens were examined for the presence of human astrovirus antigen using a monoclonal antibody-based ELISA (Astrovirus RIDASCREEN® r-Biopharm, Germany) technique. Astrovirus was detected in 40.4 percent (65/161) of the diarrhoeal stools compared to 11.1 percent (6/54) of the control specimens. Astrovirus was found to infect younger children and about three quarter of the children infected was under 12 months of age. The prevalence of infection decreases with age group and was statistically significant (P = 0.0470). Although, prevalence of infection is more in males than females but this is not significant. This study shows that astrovirus is an important agent of acute gastroenteritis among children in Lagos state.